Analysis of the Influence of Service Quality on Customer Satisfaction of ESB Application Users in the Restaurant Industry Using the Technology Acceptance Model (TAM) Method - Alviana Putri; Ismil, Ismil; Rini Sulistiyowati; Gita Cahyani Lestari (SEAN Institute, 2025)
This study aims to analyze the influence of service quality on customer satisfaction of users of Electronic Software applications. for Business (ESB) in the restaurant industry using the Technology Acceptance Model (TAM) approach. The TAM model focuses on two main constructs , namely perceived usefulness (perceived usefulness) and perceived ease of use (perceived ease of use), which is believed to influence user attitudes in accepting technology. This study used a quantitative method by distributing questionnaires to 150 respondents who were active users of the ESB application. Data were analyzed using the Structural Equation Modeling (SEM) with the help of software SmartPLS . The results of the study indicate that service quality has a significant effect on perceived ease of use and perceived usefulness, and both variables have a positive effect on customer satisfaction. This means that the better the service quality of the ESB application, the higher the customer satisfaction in using it.